The Prevalence of Hypermobility in Children with Irritable Bowel Syndrome and Functional Abdominal Pain is Similar to that in Healthy Children - Shulman, Robert J. (J Pediatr, 2020)
OBJECTIVES: To test the hypothesis that the prevalence of joint hypermobility (is greater in children with irritable bowel syndrome (IBS) and functional abdominal pain (FAP) than in healthy control children and is related to gastrointestinal symptoms and psychosocial distress (anxiety, depression, somatization). STUDY DESIGN: Children (IBS, n=109; FAP, n=31; HC, n=69), 7–12 years of age completed prospective 2-week pain and stooling diaries and child- and parent-report measures of anxiety, depression, and somatization. JH was determined using Beighton criteria (score ≥ 4 or 6). We also examined possible relationships between Beighton score, race, body mass index, gastrointestinal symptoms, and psychosocial distress. RESULTS: Beighton scores were similar between groups, as was the proportion with JH. Scores were higher in girls (3.1 ± 2.4) than boys (2.3 ± 1.8; P=0.004) and decreased with age (P < .001, r=−0.25). Race and body mass index did not impact JH prevalence. Beighton scores were not related to abdominal pain or stooling characteristics. Participants with a score ≥4 and ≥ 6 had greater somatization and depression by child report (P=0.017 and P=0.048, respectively). No association was seen for anxiety. There was no significant association between JH and psychosocial distress measures per parent report. CONCLUSIONS: Contrary to adult literature, the prevalence of JH does not differ among children with IBS, FAP, or HC. The presence or severity of JH does not correlate with abdominal pain or stooling characteristics. Somatization and depression by child report appear to have a relationship with JH.